2019
DOI: 10.1089/acm.2018.0291
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Multimodal Health Program with Diet, Art, and Biofield Therapy on the Quality of Life of People in Japan

Abstract: Objective: To investigate whether the frequency of the practice of each of diet, art, and biofield therapy influences improvement in quality of life (QOL), and to examine whether the simultaneous practice of all three components increasingly improves QOL in a real-world setting. Design: Pre–post-test design using convenience sampling methods. Setting: Home setting. Subjects: A total of 4681 individuals aged 16 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…According to the authors' study, frequent practice of the diet and/ or art components of OHWP was an independent factor associated with the improvement of QOL. Interestingly, the frequency of receiving OPT had no association [1]. These results may have been caused by differences in attitudes toward the practice of each component.…”
Section: Ohwp For Whole-person Healthmentioning
confidence: 78%
See 1 more Smart Citation
“…According to the authors' study, frequent practice of the diet and/ or art components of OHWP was an independent factor associated with the improvement of QOL. Interestingly, the frequency of receiving OPT had no association [1]. These results may have been caused by differences in attitudes toward the practice of each component.…”
Section: Ohwp For Whole-person Healthmentioning
confidence: 78%
“…In various diseases and conditions, a combination of health programs, including lifestyle interventions and psychological approaches, is often used to improve physical symptoms and Quality of Life (QOL). In the previous report entitled 'the influence of a multimodal health program with diet, art, and biofield therapy on the quality of life of people in Japan,' [1] the authors described the effectiveness of Okada Health and Wellness Program (OHWP). OHWP is a multicomponent health program that comprises the three components of diet, art, and biofield therapy (Okada Purifying Therapy [OPT]).…”
mentioning
confidence: 99%
“…17 The team reported that the regular practice of Okada Health and Wellness Program helped *80% of patients with hypertension to become normotensive, and *30% either reduced/stopped taking medication. 28 Further, simultaneous practice of OPT, diet, and art components were more likely to improve quality of life (QOL) 29 evaluated with the 10-item MOA quality of life questionnaire (MQL-10), 30 which is described further in the Methods section.…”
Section: Okada Purifying Therapymentioning
confidence: 99%